Does the recent afforestation program in Ethiopia influenced vegetation cover and hydrology? A case study in the upper awash basin, Ethiopia - Alexander Takele; Haileyesus Belay Lakew; Gizachew Kabite (Heliyon, 2022)
The Ethiopian government planned afforestation programs in the past decades whereas more attention was given to tree plantation since the 2010 year. However, the effectiveness of the afforestation programs and its impacts on vegetation cover and hydrology has not been well studied. This study aims to assess the recent campaigned afforestation program and its impact on vegetation cover and hydrology in the upper Awash basin, Ethiopia. Landsat 8 images of 2013–2020 years were used to calculate the NDVI for the upper Awash basin to assess trends in vegetation greenness for the basin. Moreover, observed streamflow and precipitation datasets of the basin were collected and used for assessing the impact of the afforestation on hydrology. The study result showed decreasing NDVI values despite the afforestation programs in the upper Awash basin. This shows either afforestation rate was less than the deforestation rate or the tree plantation campaign was not effective in the basin. In addition, the campaign based tree plantation focused on the number of tree planted not on how many trees are grown. On the other hand, mean annual precipitation and streamflow were generally increased from 2013 to 2020 in the upper Awash basin. Declining NDVI values but increasing mean annual precipitation in the Awash basin indicated that the declining vegetation was attributed to anthropogenic effects. The increasing streamflow during the same time could be due to the increasing mean annual precipitation. Moreover, the decreasing vegetation cover might have contributed for the increasing streamflow through increasing surface runoff and decreasing transpiration. However, further research is required to assess the precise impacts of afforestation on vegetation cover and hydrologic processes. Generally, the study result showed that the focus of afforestation should be on tree growing than on tree plantation alone.